A common maritime regime for the South China Sea - Sun, Kuan-Ming (Department of Public Law, 2024)
The South China Sea is a semi-enclosed sea in two respects. In terms of the geographical reality, the region is readily separable from the waters surrounding it. Moreover, it falls under the 1982 Law of the Sea Convention, which requires littoral states to cooperate in the maritime sphere. At present, a number of problems beset the region.